A study on the awareness and attitude of Bumiputra teachers in the Serian District, Samarahan, towards saving for their children's higher education / Hasanah Adon - Adon, Hasanah (2008)
Awareness and attitude has always been a very prominent issue in marketing. The main objective of this study is to determine the level of awareness and the attitude of Bumiputra teachers towards saving for their children's higher education. Besides the main objective mentioned above, this research also determined which of the demographic factor that has the strongest impact on their level of awareness and attitude towards saving for their children's higher education. The findings show that 88.9% of Bumiputra teachers teaching in the Serian District have a higher level of awareness and positive attitude towards saving for their children's higher education. The findings also show that they have knowledge on how to secure a good financial future to support their children's higher educational need. Financial institutions are therefore encouraged to tap this potential Bumiputra market by exposing their varieties of education investment plans to the Bumiputra teachers. Some recommendations are suggested on how to improve the teachers’ financial planning knowledge and saving attitude towards their children's higher education.